1998
DOI: 10.1097/00005392-199808000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Ureteropyeloscopic Treatment of 2 Cm. Or Greater Upper Urinary Tract and Minor Staghorn Calculi

Abstract: Large and complex upper urinary tract calculi can be addressed safely and efficiently with retrograde endoscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 15 publications
3
46
0
4
Order By: Relevance
“…Cumulative success rate of RIRS after multiple sessions has been reported as 77%-93% in renal stones greater than 2 cm. [9][10][11][12][13][14] Grasso et al used fiberoptic ureteroscope for noninfectious stones greater than 2 cm that were not suitable for PCNL and reported their success rate as 93%. Breda et al [9] reported a cumulative postprocedural success rate of 93% after 2.3 sessions on average in stones with a diameter of 2-2.5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative success rate of RIRS after multiple sessions has been reported as 77%-93% in renal stones greater than 2 cm. [9][10][11][12][13][14] Grasso et al used fiberoptic ureteroscope for noninfectious stones greater than 2 cm that were not suitable for PCNL and reported their success rate as 93%. Breda et al [9] reported a cumulative postprocedural success rate of 93% after 2.3 sessions on average in stones with a diameter of 2-2.5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies compared the results of PCNL and RIRS in intrarenal stones smaller than 2 cm, only a few studies have investigated their results in renal stones greater than 2 cm. [11][12][13][14][15] In 2011, Akman et al [15] studied patients with renal stones 2-4 cm in size and reported a success rate of 73.5% with a single session of RIRS and 91.2% with a single session of PCNL, and the stone-free rate was found to be 91.2% after 1.2 RIRS sessions on average. In our study, stone-free rates were 91.8% for a single session PCNL and 66.6% for a single session RIRS; however, the stone-free rate increased to 87.7% after the second session of RIRS.…”
Section: Discussionmentioning
confidence: 99%
“…As electrohydraulic lithotripter was the only one available instrument for fURS at that time, fURS was not an acceptable treatment option for large stones because of its high complication rates. Grasso et al [15] published the results of fURS with holmium:YAG laser in 45 patients in whom PCNL was contraindicated due to their comorbidities. They reported SFR after first session as 76%, while it rose up to 91% after retreatment with fURS with an overall postoperative complication rate of 2%, where they defined success as residual stone fragments smaller than 2 mm.…”
Section: Treatment Of Intrarenal Stones Larger Than 2 CMmentioning
confidence: 99%
“…The utility of this approach for larger stones remains less well-defined, although in small series has been associated with stone-free rates after a single treatment session of up to 60%. 27 When PCNL is chosen as the most appropriate form of management, preoperative planning is essential. Due to the long distance between skin and stone in obese patients, it may be necessary to use a longer access needle, working sheath and/or rigid nephroscope.…”
Section: Discussionmentioning
confidence: 99%